Can multistakeholder forums empower indigenous and local communities and promote forest conservation? A comparative analysis of territorial planning in two Brazilian states with contrasting contexts. Issue 1 (12th December 2020) - Gonzales Tovar, Jazmin; Sarmiento Barletti, Juan P.; Larson, Anne M.; Barnes, Grenville; Tucker, Catherine M.
Abstract: Multistakeholder forums (MSFs) are applied in territorial planning with the goal of bringing together diverse actors in decision‐making, allowing the participation and empowerment of indigenous and local communities, protecting their territories, and promoting community‐based conservation efforts. However, important questions remain. How are territorial planning MSFs shaped by context and power? Can they represent communities' diversity, respect their ancestral rights, and bring real change? This article explores how context and power affect the capacities and challenges of territorial planning MSFs to include, represent, empower, and benefit communities. Examining actors' perceptions, we comparatively analyze two cases, in two Brazilian states with contrasting contexts. We conclude that territorial planning MSFs are highly political spaces influenced by complexities in context, power relations, and communities' diversity. They may include, represent, and empower communities and help recognize and conserve their territories, but not necessarily. Especially in difficult settings, communities face more challenges than other actors to be represented and participate at MSFs, and territorial planning may empower or "invisibilize" communities. Other mechanisms (e.g., social action) can be key for communities instead of, or in synergy with, MSFs.